Having a Mary heart in a Martha world : finding intimacy with God in the busyness of life - Weaver, Joanna (Colorado Springs, Colo. : WaterBrook Press, 2000)
With her fresh approach to the familiar Bible story, Joanna Weaver shows how all of us - Marys and Marthas alike - can draw closer to our Lord: deepening our devotion, strengthening our service, and doing both with less stress and greater joy.
Includes bibliographical references.
Keywords: Christian women -- Religious life